Potensi pariwisata keraton kasunanan surakarta di tinjau dari daya tarik, lokasi dan promosi - Septian Haryoko; Ida Aryati; Ratna Damayanti (ITB AAS INDONESIA Surakarta, 2020)
The purposeFof thisPstudy aimsPto determinePthe effect of Attraction Data, Location and Promotion of the Tourism Potential of the Surakarta Sultanate Palace. This type ofPresearch is a quantitative description. ThePpopulation inPthis studyIwere visitors to the Surakarta Kasunanan Palace, amounting to 1223 using Purposive Sampling with 100 respondents.0This studyPuses dataPanalysis techniques inNthe formPof multiplePlinear regression tests. ThePresults of this studyKindicate that: (1) There is an influence of Attractiveness on Tourism Potential of Surakarta Palace of Kasunanan which is indicated by the regression5coefficient value of 4.061 and the0significance value is smaller thanPthe levelPof significantG(0,000 0.050), and (3) There is an influence on the Promotion of the Potential Surakarta Palace Keraton Tourism indicatedPby a regressionPcoefficient of 3.249 andPSignificance valuePis smaller thanPthePlevel of significant (0.002